Internacionalização via redes de negócio: um estudo de caso de subsidiária japonesa no Brasil em expansão para América Latina e Caribe - Souza Filho, Normando Rodrigues de (2012)
The objective of this dissertation is to analyze the relevance of business network theory in internationalization strategies of multinational firms. The starting point are the operations of the Brazilian subsidiary, which aims to lead the process of internationalization to South America and the Caribbean. The aim is to understand the relationships between the actors and how this influence and contribute to the internationalization of the company. Over the past 40 years studies in International Business have expanded as a result of the internationalization process of companies with different activities around the world. Initially, the scientific production came out from the University of Uppsala. Later the relationship between the environment and the organization has gained importance and has emerged the theory of business network. These relationships go beyond the boundaries of the firm, because they consider the foreign trade relations. Thus, in this context, we will highlight the business network of the Brazilian subsidiary and its relations with local actors. The survey was conducted through a single case study of a multinational Japanese company with more than a century of existence, from its Brazilian subsidiary which dates back to 50 years. We collected secondary and primary data, as well as in depth interviews with executives in the cities of Sao Paulo, Buenos Aires and Panama. This collection aimed to elucidate the research problem. For this purpose, a software for social network analysis was also used to assist in mapping the business network and identifying key actors. The results shows that the assumptions advocated by the theory of business network, as for the aspects related to internationalization through the network of relationships, trust, knowledge and relationship with the actors are real. It was possible to verify the company's business expansion into new markets through the relationship built with relevant actors of the network, and it was evident the importance of trust in this process